Effects of Cobalt Source on Rate and Extent of Dry Matter and Fiber Degradation in Vitro - F. Vargas-Rodriguez; Gail Carpenter; J. DeFrain; B. Bradford (Kansas Agricultural Experiment Station Research Reports, 2015)
Positive effects on fiber degradation have been observed when supplemental cobalt was fed to ruminants. This study tested the effects of cobalt carbonate (CoCarb) and cobalt glucoheptonate (CoGH) at different concentrations on in vitro fermentation rate, fermentation end-product concentrations, and degradation of feed dry matter and neutral detergent fiber. Compared to CoCarb, CoGH increased dry matter disappearance and neutral detergent fiber degradation when added at 1 part per million (ppm) cobalt or less. Furthermore, CoGH had limited effects on the biohydrogenation of long chain fatty acids, whereas CoCarb appeared to stimulate this process when added at more than 3 ppm cobalt. Cobalt is not only an important precursor for vitamin B12 synthesis, but it also influences ruminal fermentation, with effects that depend on its chemical form.
Keywords: minerals; digestibility; fiber; gas production